The Effects of Morphological Productivity on Word Recognition - Przewłoka, Zuzanna (My University, 2015)
As readers, writers, speakers and listeners, we come across newly formed words on a regular basis throughout our lives. Often, we have not heard these words, and they cannot be found in dictionaries. Because we understand the meaning of different morphemes (word parts) and how they can be put together to form complex words, we are able to understand these novel words and infer their meaning. How is it that we can see or hear words previously unknown to us and infer their meaning with relative ease? Past research (e.g. Hay & Baayen, 2001) has suggested that multi-morphemic words can be recognized via decomposition, by being broken down into their morphemic components, or via their full word form. The route taken during recognition can be affected by a multitude of factors, including a concept known as morphological productivity (Schreuder & Frauenfelder, 1991). Being a measure of an affix’s likelihood to create new words, productivity may be used to explain novel word recognition. By using the masked priming paradigm and EEG measures to compare the recognition of productively and unproductively suffixed words, this study showed N400 effects for productively suffixed words, which argues that decomposition takes place during recognition of these words. The N400 effect suggests the presence of decomposition during recognition of productively suffixed words, which implies that novel words are likely recognized via decomposition.
Keywords: affix productivity; decomposition; full-listing; dual-route; morphology